Multi-wavelength 128 Gbit s−1λ−1 PAM4 optical transmission enabled by a 100 GHz quantum dot mode-locked optical frequency comb. (4th January 2022) - Pan, Shujie; Zhang, Hongguang; Liu, Zizhuo; Liao, Mengya; Tang, Mingchu; Wu, Dingyi; Hu, Xiao; Yan, Jie; Wang, Lei; Guo, Mingchen; Wang, Zihao; Wang, Ting; et al.
Abstract: Semiconductor mode-locked lasers (MLLs) with extremely high repetition rates are promising optical frequency comb (OFC) sources for their usage as compact, high-efficiency, and low-cost light sources in high-speed dense wavelength-division multiplexing transmissions. The fully exploited conventional C- and L- bands require the research on O-band to fulfil the transmission capacity of the current photonic networks. In this work, we present a passive two-section InAs/InGaAs quantum-dot (QD) MLL-based OFC with a fundamental repetition rate of ∼100 GHz operating at O-band wavelength range. The specially designed device favours the generation of nearly Fourier-transform-limited pulses in the entire test range by only pumping the gain section while with the absorber unbiased. The typical integrated relative intensity noise of the whole spectrum and a single tone are −152 and −137 dB Hz −1 in the range of 100 MHz–10 GHz, respectively. Back-to-back data transmissions for seven selected tones have been realised by employing a 64 Gbaud four-level pulse amplitude modulation format. The demonstrated performance shows the feasibility of the InAs QD MLLs as a simple structure, easy operation, and low power consumption OFC sources for high-speed fibre-optic communications.